ANALISA DINAMIS PADA PORTAL GEDUNG BERTINGKAT TERHADAP BEBAN GEMPA SESUAI SNI 1726:2019 WILAYAH KOTA PALU - M. Zain, Arzal; Widodo, Eko; Arlangga, Moh. Nugar (Surya Teknika, 2024)
Dynamic Analysis of Multi-storey Building Portals towards Earthquake Loads According to SNI 1726:2019 in Palu City. We ofien feel the ground surface vibrations due to earthquakes which have an impact on high-rise building structures and s concrete avidence that our country is mostly located in earthquake areas. According to the earthquake resistance planning guidelines forhauses and buildings (SNI 1726:2019), dynamic analysis can be carried out by analyzing the variety of response spectrum. The shear resisting structure only takes into account horizontal forces and lateral deflections. The magnitude of displacement, the shape of the structural change depends on the size of the ratio between the mass and the stiffness of the column. The matrix method playsa very important rorein determining the CicularNatural Frequency (?) and the shape og the structure change (mode shape) and the superposition mode plays a role in superposing the acting forces with the displacement to a simpler from. Basiccally, the actual earhquake force is significantly difficult to predict, butthe analysis approach is to obtain the design earthquake force that the structure can bear.